Pengaruh CSR, Struktur Modal dan TATO Terhadap Kinerja yang Berdampak pada Nilai Perusahaan Consumer Goods - Eklesia Theodora Octavia Sitompul; Diyan Lestari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of corporate social responsibility, capital structure, and total asset turnover on performance and firm value in consumer goods companies that listed in IDX from 2014-2018. This study used 35 companies as sample research and considered the associative method with quantitative approach. The secondary data is used in this research to analyze the relationship among variables. The data was obtained from the companies annual reports which can be accessed from the Indonesia Stock Exchange (IDX) sites and other official sites. The result of this study indicates that CSR, capital structure, and total asset turnover influence the corporate performance, but CSR, capital structure, and TATO do not affect the firm value. While CSR, capital structure, and TATO influence the firm value with financial p erformance is found as the intervening variable.